Aktivitas Antibakteri Ekstrak Etanol Kulit Markisa Ungu (Passiflora Edulis Sims) Terhadap Bakteri Propionibacterium Acnes - Karnirius Harefa; Barita Aritonang; Ahmad Hafizullah Ritonga (Jurnal Multidisiplin Madani, 2022)
Propionibacterium acnes is a gram-positive bacterium that causes acne. This study aimed to determine the antibacterial activity of the ethanolic extract of purple passion fruit peel (Passiflora edulis Sims) against Propionibacterium acnes bacteria. The method used to determine the antibacterial activity of the ethanolic extract of passion fruit peel was a paper disc (Kirby-Bauer test). Based on the results of phytochemical screening, the purple passion fruit peel simplicia powder contains flavonoid compounds, saponins, tannins, steroids, and triterpenoids that function as antimicrobials. Based on the antibacterial activity test, the purple passion fruit peel ethanol extract at concentrations of 5, 10, 15, and 20% effectively inhibited the growth of Propionibacterium acnes bacteria. This can be proven from the results of the diameter of the inhibition zone that there was an increase in antibacterial effectiveness along with the increase in the concentration of purple passion fruit peel extract in inhibiting the growth of Propionibacterium acnes bacteria, namely at a concentration of 5%, the average diameter of the inhibition zone was 14.9 mm, then at a concentration of 10% the average diameter of the inhibition zone is 15.3 mm, then at a concentration of 15% the average diameter of the inhibition zone is 17.2 mm, while at a maximum concentration of 20% the average diameter of the inhibition zone is 20.1 mm. The research results conclude that the purple passion fruit rind ethanol extract effectively inhibits the growth of Propionibacterium acnes bacteria at a concentration of 20% with an inhibition zone diameter of 20.1 mm.